Molecular detection of integrated reticuloendothelial virus genes in fowlpox virus field isolates and live vaccines of poultry - RAJASEKARAN, RANJANI; KIRUBAHARAN, J JOHN; RAJALAKSHMI, S; VIDHYA, M (The Indian Journal of Animal Sciences, 2019)
Two field isolates (FWPV-W1 and FWPV-W2) obtained from unvaccinated backyard poultry chickens and four commercial live vaccines (FWPV-G, FWPV-V, FWPV-B and FWPV-H) of fowlpox virus origin were isolated on chorio-allantoic membrane (CAM) of embryonated chicken eggs. The CAM tissues infected with FWPV-W1, FWPVW2, FWPV-G, FWPV-V, FWPV-B and FWPV-H individually were subjected to DNA isolation. The isolated DNA was tested for the presence of P4b gene by PCR to confirm FWPV. Then, each of the field isolates and commercial vaccines were screened for presence of reticuloendothelial virus envelope (REV-env) gene and long terminal repeat (LTR) region by PCR. FWPV-W1 isolate was positive for REV-env gene (807 bp) and REV-LTR region (370 bp), which confirmed presence of near full-length REV integration in its genome. Whereas, FWPV-W2 isolate was positive for LTR region and negative for REV-env gene. This suggested that full-length REV is not present in all FWPV field isolates. All the four commercial live vaccines, were negative for REV-env gene. This showed that full-length REV is absent in these commercial vaccines, ensuring safety of the usage of these vaccines in India. However, the commercial vaccines were positive for REV-LTR region, which does not affect the vaccine safety.